1978
DOI: 10.1093/geronj/33.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Training and Oxygen Conductance in the Elderly I. The Respiratory System

Abstract: Static lung volumes, closing volumes and pulmonary diffusing capacity have been measured in a group of 19 subjects (9 M, 10 F) 60 - 76 years old, all volunteers for an exercise training program (nominal 4 hours per week for 11 weeks). Initial static lung volumes were larger than in some previous series, perhaps because our sample was health-conscious and mainly nonsmokers. Training produced no significant changes in any of the pulmonary variables tested, despite a 10% increase of maximum oxygen intake seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…These findings are in line with animal studies showing that chronic exercise training does not affect pulmonary diffusion capacity (58,59,456) or the morphological dimensions of the pulmonary diffusion surface (456). Static lung volumes of endurance trained subjects are also not different compared to those of sedentary individuals (67,330,342), and physical training does not cause significant changes in these parameters (391,442,485).…”
Section: Lungs and Airwayssupporting
confidence: 88%
“…These findings are in line with animal studies showing that chronic exercise training does not affect pulmonary diffusion capacity (58,59,456) or the morphological dimensions of the pulmonary diffusion surface (456). Static lung volumes of endurance trained subjects are also not different compared to those of sedentary individuals (67,330,342), and physical training does not cause significant changes in these parameters (391,442,485).…”
Section: Lungs and Airwayssupporting
confidence: 88%
“…Other investigators have reported that the decline in fat free mass accounts for ∼35% of the decline in VO 2 max [9]. It is clear that the maximal cardiac output declines with aging but whether muscle oxidative capacity (which is a major determinant of A-VO 2 difference) declines with aging is a question that is presently under scientific debate.The results of early studies of aerobic exercise training in the elderly suggested that there was little adaptation in aerobic capacity [10][11][12][13]. These early studies have been criticized as a result of the exercise intensity being inadequate to stimulate adaptation.…”
mentioning
confidence: 99%
“…The values obtained both in absolute terms and expressed in terms of body weight fit well into the ex pected range for elderly men [Benestad, 1965;Niinimaa and Shephard, 1978], Since we do not know with certainty whether the asymp totic relationship of fH to VO2 applies to elderly subjects [cf. Benestad, 1965] it is pos sible that we have overestimated VO2 max and underestimated the relative work-load.…”
Section: Discussionmentioning
confidence: 54%